2017
DOI: 10.1002/cncr.30953
|View full text |Cite
|
Sign up to set email alerts
|

Pathological complete response in patients with esophageal cancer after the trimodality approach: The association with baseline variables and survival—The University of Texas MD Anderson Cancer Center experience

Abstract: In this large cohort study, a pathCR is confirmed to be associated with better OS and RFS. The presence of a poorly differentiated tumor or SRCs reduces the likelihood of a pathCR. Future research should focus on molecular classifiers. Cancer 2017;123:4106-4113. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
112
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(128 citation statements)
references
References 29 publications
13
112
3
Order By: Relevance
“…Certain clinical factors are associated with lower or higher probability of pCR. Among clinical factors associated with lower pCR are older age (>60), poorly differentiated histology, presence of signet ring cells, higher T stage, and adenocarcinoma subtype [13]. Based on the findings of this study, other than the histological subtype, the patient had none of these oncologic factors, which in retrospect indicated a relatively high pretreatment probability of pCR.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Certain clinical factors are associated with lower or higher probability of pCR. Among clinical factors associated with lower pCR are older age (>60), poorly differentiated histology, presence of signet ring cells, higher T stage, and adenocarcinoma subtype [13]. Based on the findings of this study, other than the histological subtype, the patient had none of these oncologic factors, which in retrospect indicated a relatively high pretreatment probability of pCR.…”
Section: Discussionmentioning
confidence: 57%
“…Locally advanced esophageal cancer patients have the option of undergoing triple therapy which includes concurrent neoadjuvant chemoradiation followed by esophageal resection [12]. A minority subset of patients undergoing triple therapy may achieve pathologically complete response (pCR) with studies indicating a range of 19-30% with a lower rate in adenocarcinoma [13][14][15][16][17][18][19][20]. Such patients enjoy favorable prognoses compared to their non-pCR achieving counterparts in terms of recurrence-free survival and overall survival [14,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…This method is the standard approach in patients with grades IB, II, III and IVA cancer [6]. Based on the various clinical trials performed, this method of treatment has been approved and confirmed by first grade clinical evidence [7]. Based on gathered evidence, 15 to 30 percent of the patients treated with neoadjuvant chemotherapy show complete pathological remission, as so the tumor itself is completely treated and no longer exists.…”
Section: Introductionmentioning
confidence: 99%
“…But even patients who have attained a complete pathologic response to neoadjuvant chemoradiation frequently fail systemically, albeit less so than incomplete responders. 3 It is important to recognize that the presence of nodal disease and response to therapy is reflective of prognosis because it is an indicator of systemic disease. The problem is that we have yet to fully address hematogenous spread.…”
mentioning
confidence: 99%